2011
DOI: 10.5402/2011/215950
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of Round HerringEtrumeus teres(Dekay,1842) from the Egyptian Mediterranean Water at Alexandria

Abstract: Maturity stages of round herring Etrumeus teres were divided anatomically into six stages. Monthly distribution of such maturity stages showed that E. teres had prolonged spawning season extended from December to May for females and to July for males. The observed sex ratio was 1 : 2 (male: female). Gonadosomatic index (GSI) values were high during breeding season for both sexes. Hepatosomatic index (HIS) values for females increased from December to April and from December to July for males. Both sexes of E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
(32 reference statements)
4
10
0
Order By: Relevance
“…So, the GSI is almost higher for females than males, particularly during spawning season which is opposite to Gulf of Suez population result. Such finding was reported for some fishes such as the round herring Etrumeus teres by El-Sayed (1996);Farrag (2010) and Osman et al (2011).…”
Section: Seasonal Variations In Maturity Stagessupporting
confidence: 75%
“…So, the GSI is almost higher for females than males, particularly during spawning season which is opposite to Gulf of Suez population result. Such finding was reported for some fishes such as the round herring Etrumeus teres by El-Sayed (1996);Farrag (2010) and Osman et al (2011).…”
Section: Seasonal Variations In Maturity Stagessupporting
confidence: 75%
“…The eggs of E. wongratanai have been seen in small numbers throughout summer off the east coast of South Africa, with peaks in abundance being observed from June to December (Connell, 2001). Winter spawning of E. wongratanai agrees with observations by Farrag (2010) and Osman et al (2011), who suggested that spawning E. golanii need a higher energy input in order to meet the physiological demands of reproduction (Froese & Pauly, 2000). Observations on the condition factor of E. wongratanai are in accordance with such for E. golanii (Fahay, 1983;Shaw & Drullinger, 1990).…”
Section: Condition Factor and Reproductive Seasonsupporting
confidence: 85%
“…The length at first maturity of E. wongratanai is greater than that of E. golanii in the Mediterranean Sea (El‐Sayed, ; Osman et al ., ), but smaller than that of (males) E. golanii in the Gulf of Suez (Table ; Sanders et al ., ). Differences in length at maturity between studies on the same species (Table ) probably depend on the environmental conditions under which maturation takes place and the nature of the population (density‐dependent growth) when length at maturity is determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations